ANALISIS DAMPAK KREDIT MACET DAN PENYALURAN KREDIT TERHADAP PROFITABILITAS BANK PERSERO - Dewi Sri Maulydia; Setiawati, Ririt Iriani Sri (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2024)
Conventional banking including Persero Bank has its main income from interest on loans distributed to the public. The purpose of this study is to prove the impact between credit congestion and credit distribution with profitability at Persero Bank in the 2013-2023 period. The source of the data for this research are from Financial Service Authority and annual financial reports of each bank. This research uses multiple linear regression as an analysis method. The result of this research prove that partially credit congestion has a negative and significant impact on profitability of Persero Bank. Meanwhile credit distribution partially hasn’t impact on profitability of Persero Bank. Simultaneously, credit congestion and credit distribution have an impact on profitability of Persero Bank.